Inferring Disease-Associated Microbes Based on Multi-Data Integration and Network Consistency Projection - Fan, Yongxian; Chen, Meijun; Zhu, Qingqi; Wang, Wanru (Frontiers in Bioengineering and Biotechnology, 2020)
Plenty of microbes in our human body play a vital role in the process of cell physiology. In recent years, there is accumulating evidence indicating that microbes are closely related to many complex human diseases. In-depth investigation of disease-associated microbes can contribute to understanding the pathogenesis of diseases and thus provides novel strategies for the treatment, diagnosis, and prevention of diseases. To date, many computational models have been proposed for predicting microbe-disease associations using available similarity networks. However, these similarity networks are not effectively fused. In this study, we proposed a novel computational model based on multi-data integration and network consistency projection for Human Microbe-Disease Associations Prediction (HMDA-Pred), which fuses multiple similarity networks by a linear network fusion method. HMDA-Pred yielded AUC values of 0.9589 and 0.9361 ± 0.0037 in the experiments of leave-one-out cross validation (LOOCV) and 5-fold cross validation (5-fold CV), respectively. Furthermore, in case studies, 10, 8 and 10 out of the top 10 predicted microbes of asthma, colon cancer and inflammatory bowel disease were confirmed by the literatures, respectively.